La viscosupplementazione - Bottiglieri, A.; Contini, A.; Di Fino, C.; Toro, G. (Lo Scalpello - Journal, 2019)
VISCOSUPPLEMENTATION Viscosupplementation is a therapeutic strategy widely used in clinical practice for the treatment of osteoarthritis, but it is still performed in a very arbitrary way as concerns the indications, doses and therapeutic scheme. At present, the scientific literature is full of studies of low scientific impact and the international guidelines show this lack of evidence. The results of the viscosupplementation consensus conferences provide useful advice for using this treatment option in clinical practice in the most correct and uniform way.